SCHOOL HISTORY EDUCATION IN THE TEMPORARY OCCUPIED TERRITORIES OF UKRAINE (2014 – 2022): IDEAS OF “RUSSIAN WORLD” AGAINST THE CONCEPT OF THE UKRAINIAN STATE - BONDARENKO , Polina; STUKANOVA , Yuliia (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to analyze the course “History of Motherland” at schools on temporary occupied territories of Donetsk region. On the basis of the overview of syllabus contents in general and the stages of Ukrainian state-building in particular, the authors have highlighted a manipulative nature of syllabus and identified hybrid threats as consequences of its applying. Research Methodology. The authors make conclusions considering the fact that school education has a huge impact on shaping the worldview and mounding opinions of a person. The study is based on civilizational and anthropocentric approaches, the method of content analysis has been applied. Scientific Novelty. An attempt to analyze the content and purpose of historical education at secondary schools on the temporarily occupied territories of Donetsk region has been made in historiography of Ukraine for the first time. Conclusions. Teaching History in the occupied territories is an important component of the Russian propaganda aiming at forming the Russian identity among young people. By twisting past events students are convinced that they are part of “Russky mir” (Russian world). Primarily, it refers to elimination of the events, connected with Ukrainian state formation, as well as the lack of information about national rebirth and national identity which is supposed to be the basis of the Ukrainian modern nation formation. Moreover, the Ukrainian past of Donetsk region is either hidden or distorted in favour of Putin’s ideology which creates a complete rejection of their own history and Ukrainian identity among young people. As a result, anti-Ukrainian nature of the educational course aims at eliminating their own historical memory among students and impose a new made-up one which is beneficial to Russia. Taking into consideration the above mentioned, today one of the main tasks of the Ukrainian historians is to find the ways to combat Russian information propaganda as school History course in the temporarily occupied territories can definitely be classified as information-propaganda tool of Russia’s hybrid warfare against Ukraine. Key words: school history education, temporarily occupied territories, hybrid threats, “Russky mir”, historical instrumentalization, civilizational approach.